El presente y futuro de la libertad de conciencia y de religión en la Unión Europea - Ettmueller, Eliane Ursula (UNISCI Discussion Papers, 2007)
This article intends to develop the current state of freedom of conscience and religion in the European Union juridical institutions. It briefly explores their evolution along the history of the EU, analyzing the jurisprudence, the European Convention on Human Rights and Fundamental Freedoms, reflecting on the constitutional traditions of the member states, presenting the advances introduced by the Maastricht and Amsterdam Treaties, and interpreting the Charter of Fundamental Rights and Liberties of the European Union and the Treaty Establishing a Constitution for Europe. The conclusions present some possible perspectives for the future.